PEDAGOGICAL IMPROVISATION IN FORMING PROFESSIONAL COMPETENCE OF THE FUTURE TEACHERS-PHILOLOGISTS - Vinnichuk, Alla; Bohatko, Valentyna; Zavalniuk, Inna; Petrovych, Olha (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The article analyzes the concept of pedagogical improvisation, clarifies its content, functions and types, determinates its role in developing professional competence of students-philologists. During the research we used the following methods: observation, analysis, interviews, mathematical statistics. The aspects of preparation of future teachers-philologists for pedagogical improvisation are highlighted, and their preparedness criteria are defined. The methodological tools of research into the level of students' ability to pedagogical improvisation are selected. The relevance of the topic is confirmed by the results of the survey of the students-philologists who are diagnosed with the level of ability to pedagogical improvisation both in the conditions of the traditional form of education and in the distance learning mode. 205 students of the specialties 035 «Philology» and 014 «Secondary Education» (Ukrainian language and literature) of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University took part in the experiment. By means of experimental activities, the features of the influence of the pedagogical improvisation on the formation of professional competence of future teachers-philologists have been identified. It was found that the level of ability to pedagogical improvisation of students-philologists in the conditions of traditional education is higher than in the conditions of excessive stay in the virtual educational space. A step-by-step algorithm of using improvisation for development of the future teachers-philologists’ professional competence in the context of blended learning is developed.